(untitled) (Revista do Centro de Estudos Portugueses, 2014)
Reconstituição histórico-crítica dos principais aspectos humanistas e interventivos da poesia e da poética de Ruy Cinatti e dos poetas reunidos em torno dos Cadernos de Poesia. O ensaio pretende identificar e reflectir sobre os processos testemunhais da poesia portuguesa dos anos 40-50 do século XX, a partir da leitura de textos programáticos dos autores mais decisivos da época. Historical-critical reconstitution of the main aspects humanist and interventional of poetry and the poetic of Ruy Cinatti and others poets gathered around Cadernos de Poesia. The essay intends to identify and reflect about the witness’s process of Portuguese poetry of the decade of 1940-1950 of XX century, from the reading programmatic texts of the most decisive authors of the time.